The effect of dark tetrad personalities traits in cyber aggression behavior among Johor Bahru teachers - Mohamed Yatim, Nur Amirah (HRMARS, 2020)
This article was published, to identify and understand the roles of Dark Tetrad personality trait in cyber aggression behavior. Although social media offer much benefit and positivity, there is an increasing observable claiming that the social media possess a huge risk, for individual, communities, firm (either profit or non-profit organization), and eventually towards the society as a whole. According to the statistics by Malaysia Computer Emergency Response Team (MyCERT) (2020), the reported cases by the computer securities and cyber aggression related incidents in Malaysia has increase from 2016 to July 2020. There are some issues regarding on Malaysian teachers issuing negative statements in Facebook. Many study has been conducted in determining the Dark Triad personality association with the cyber aggression behavior. This study aims to examine the Dark Tetras personality traits that contributed to the cyber aggression behavior among teachers. This study has been conducted among 169 participants, which is the civil servant – teachers in Johor Bahru, Malaysia. The respondent has been chosen, as teachers represent the highest number of Malaysian civil servant. The study has been conducted quantitatively, and a sets of questionnaire, has been distributed via google doc to the respondents. The result shown that there has a significant relationship between the 4 construct in the Dark Tetrad personality with the cyber aggression behavior, whereby Psychopathy has become the highest element (based on the mean score) among the four Dark Tetrad personality traits. This study is expected to prove the Dark Tetrad personality conceptually; but the empirical evidence from the study can be used in order to facilitate more detailed future studies especially in dark personalities fields. It is also expected to improve understandings of the dark personalities of the teachers; as they are the role models in schools in order to increase the education quality in Malaysia, in tandem with the Malaysia Education Development Plan.